Are Basic School Head Teachers Transformational Leaders? Views of Teachers - Kwame Bediako Asare (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2017)
Transformational leadership practice is associated with improved school functioning and quality education delivery through teacher commitment and willingness to exceed targets or educational benchmarks (Balyer, 2012; Nedelcu, 2013).  The establishment of the  Leadership for Learning (LFL) program in Ghana in 2009 aimed at improving the effectiveness of basic school head teachers to better lead schools to promote student learning.  In this study, the perceptions of basic school teachers as to the transformational leadership conduct of head teachers who had received training under the LFL model were collected and reviewed.  The purpose of this qualitative inquiry was to determine from teachers' perceptions how the conduct of head teachers related to transformational leadership.  From the study results, the findings indicated that while teachers largely perceived their head teachers as transformational leaders, more than the influence of head teachers is required to motivate teachers to give of themselves to improve education outcomes. Recommendations and implications of the study for practice and research were considered.